MENINGKATKAN KETERAMPILAN MEMBACA NOTASI ANGKA SECARA VOKAL DENGAN METODE DRILL PADA SISWA SMP - Ela, Leonila; istiandini, Winda; Muniir, asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to improve students' skills in reading vowel notation through the drill method. The form of this study is classroom action research. The subject of this research were 34 students of class VII B. This study was conducted in 2 cycles. Each cycle consists of 4 stages, namely, planning, implementation, observation, and reflection. The research instruments were in the form of observation sheets and skill test sheets. The results of the research in the first cycle of students have not been right to read the number notation according to the indicator. While reading the number notation there are still many students who say the solmization is not in accordance with the not symbol. Students do not correctly place the fis chromatic pitch height. Students have not been able to read notes according to the high and low notes on the picth indicator. Then students have not been right to ring according to the not value indicator. In cycle II students show changes in reading numeric notation with the accuracy of reading the solmization according to the symbol of the not, can place chromatic tones according to the level, can sound the tone according to the pitch and pitch, and students have been able to sound the number notation according to the note. It can be concluded that through the drill method can improve students' skills in reading number notation.Â Keyword: Improvement, Number Notation, Vocals, Drill Method. Â